Estimating Mean Residence Time of Groundwater in Central Basin/Erbil using Environmental Isotopes - Bruska S. Mamand; Dana K. Mawlood (Zanco Journal of Pure and Applied Sciences, 2023)
The average time of input water needs to recharge the groundwater basin and reach a catchment outlet, whether it follows a vertical or horizontal flow direction, is known as the mean residence time (MRT). This study aims to identify the theory concepts of estimation MRT of groundwater in a well using environmental isotope technique. For this purpose, the spatiotemporal data of oxygen-18 of precipitation in Erbil city were taken from Global Network of Isotopes in Precipitation (GNIP). Furthermore, a well named (HWL) in Erbil city that located at central basin of groundwater were selected. Because of δ18O measured as a natural tracer for estimation MRT in groundwater, the sample analyzed for isotope by using the cavity ring down spectrometer. The derivation of sine wave regression was used to measure δ 18O variations in both precipitation and groundwater. Decreasing isotopic amplitude of δ18O due to the phase shift from input (precipitation) which is 5.74 ‰ to output (groundwater) to 0.277 ‰ can solve by sine wave equation to estimate MRT of groundwater in aquifer. Results showed that, by temporal response of groundwater to precipitation inputs, MRT from HWL well in Erbil city estimated was 1202 days. This concluded that groundwater spent about 1202 days for recharging HWL well. 2The comparison of δ18O in precipitation and groundwater in Erbil city range from -10.1 to -2.4 per mill for rainfall. These values varied from -7.05 to -6.86 when inters groundwater from HWL well which are typically affected by a reflection of the current state climates.